Factors predictive of locoregional recurrence following neoadjuvant chemotherapy in patients with large operable or locally advanced breast cancer: An analysis of the EORTC 10994/BIG 1-00 study. (July 2017) - Gillon, Pauline; Touati, Nathan; Breton-Callu, Christel; Slaets, Leen; Cameron, David; Bonnefoi, Hervé
Abstract: Purpose: Identification of clinicopathological factors predicting for a locoregional recurrence (LRR) after neoadjuvant chemotherapy (NAC) could help to decide on the optimal locoregional radiotherapy. The objective of this trial is to identify those factors in the context of a phase III trial (European Organisation for Research and Treatment of Cancer 10994). Methods: Patients received NAC followed by surgery with or without radiotherapy. Radiotherapy was administered according to pre-specified guidelines. Patients with hormone receptor positive tumours received adjuvant hormonal therapy. A proportion of patients with human epidermal growth factor receptor 2 (HER2) positive cancer received adjuvant trastuzumab. The predictive factors for LRR were identified by multivariate analysis with time to LRR as first event as the primary end-point. Results: The median follow-up was 4.4 years. In 1553 eligible patients, there were 76 LRRs with a 5-year cumulative incidence of 4.9% (95% confidence interval, CI [3.76–6.04]). In multivariate analysis, breast cancer subtype was a significant predictor of LRR (p < 0.0001): hazard ratio (HR) 6.44 (95% CI [2.83–14.69]) for triple negative, 6.26 (95% CI [2.81–13.93]) for HER2+ without trastuzumab (T) and 3.37 (95% CI [1.10–10.34]) for HER2+ with T cancers, all compared to luminal A patients. Lack of pathological response was also associated with significantly higher LRR risk in case of ≥4 pathologically positive nodes, HR 2.43 (95% CI [1.34–4.40], p < 0.0001). Conclusion: Breast cancer subtype and lack of pathological response are predictive factors for high LRR after NAC. Highlights: Predictors of locoregional recurrence (LRR) may help to tailor radiotherapy. Second study using data from a prospective trial. Low 5-year LRR rate (4.90%), with only 76 patients with a LRR as first event. The highest LRR risk is observed in triple negative and HER2+ subtypes.